The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1021/jm00388a032
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl derivatives of the 5-HT2 agonist 1-(4-bromo-2,5-dimethoxyphenyl)-2-aminopropane

Abstract: 1-(4-Bromo-2,5-dimethoxyphenyl)-2-aminopropane (DOB) is a serotonin (5-HT) agonist that displays a high affinity and selectivity for a certain population of central 5-HT binding sites (i.e., 5-HT2 sites). In the present study, (a) an enantiomeric potency comparison was made for the optical isomers of DOB and (b) the activity of N-monomethyl-,N,N-dimethyl-, and N,N,N-trimethyl-DOB was examined. (R)-(-)-DOB (Ki = 0.39 nM) was found to have 6 times greater affinity than its S-(+) enantiomer at [3H]DOB-labeled (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This observation is in agreement with other hallucinogenic phenylalkylamines where a primary amine exhibited higher hallucinogenic potency which correlates with higher affinity to 5-HT 2 receptors [19]. It has been reported that the N,N-dimethyl and N-monopropyl analogs of DOB (1-(4-bromo-2,5-dimethoxyphenyl)-2-aminopropane), the brominated counterpart of DOI, showed significant decrease in 5-HT 2A receptor affinity [20,21]. Glennon et al [19] compared affinities of DOB, the N-monomethyl analog and the N-benzyl derivative for 5-HT 2A and 5-HT 2C .…”
Section: Radiosynthesissupporting
confidence: 89%
“…This observation is in agreement with other hallucinogenic phenylalkylamines where a primary amine exhibited higher hallucinogenic potency which correlates with higher affinity to 5-HT 2 receptors [19]. It has been reported that the N,N-dimethyl and N-monopropyl analogs of DOB (1-(4-bromo-2,5-dimethoxyphenyl)-2-aminopropane), the brominated counterpart of DOI, showed significant decrease in 5-HT 2A receptor affinity [20,21]. Glennon et al [19] compared affinities of DOB, the N-monomethyl analog and the N-benzyl derivative for 5-HT 2A and 5-HT 2C .…”
Section: Radiosynthesissupporting
confidence: 89%
“…[171] Binding studies using [ 3 H]DOB (16) as a radioligand indicated R-(À)-16 (K i = 0.39 nm) as the highest affinity enantiomer, followed by (AE )-16 (K i = 0.79 nm), and S-(+)-16 (K i = 2.3 nm). [172] Similarly, a DD assay in the same study found R-(À)-16 to be~10 times more potent than S-(+)-16. The same pattern was seen for compound 17, where the R-(À) isomer is 2-3 times as potent as the S-(+) enantiomer.…”
Section: Wwwchemmedchemorgmentioning
confidence: 89%
“…N-alkylation or N,N-dialkylation proved detrimental to the potency of most phenylalkylamines. [172,174,175] An exception was found in a series of N-benzyl substituted phenylalkylamines; [176] affinity studies comparing 2C-B (11) with its N-benzylated analogues (29-31) revealed an approximate twofold increase in binding affinity for [ 125 I]DOI labeled 5-HT 2A receptors. Moreover compounds 29-31 showed increased subtype selectivity (> 100 fold) for 5-HT 2A over 5-HT 2C receptors, however the question whether 29-31 act as agonists or antagonists has not been addressed.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%
“…DOB was administered i.p. 15 min prior to the test session (Glennon et al 1987) and 8-OH-DPAT was administered s.c. 15 min prior to the test session with the 0.3-mg/kg training dose of nicotine.…”
Section: Apparatusmentioning
confidence: 99%